Interactive E-learning environment for learning BJT via simple project - Muhammad `Arif Bin Abdul Malek (Nanyang Technological University, 2024)
This project's main objective is to facilitate vivid visualization and comprehension of previously hard to understand concepts and content on Bipolar Junction Transistors (BJT) through an E-Learning environment for students to be able to comfortably grasp the knowledge of BJT at their own pace